Analisis Perbandingan Kinerja Layanan Infrastructure As A Service Cloud Computing Pada Proxmox dan Xenserver - Surahmat Surahmat; Alfred Tenggono (Universitas Bumigora, 2019)
Cloud computing is a technology that utilizes the internet as a service so that it does not use too many physical computers because the cloud computing system uses a virtual system where by using a computer alone it can provide services to many computers at the same time with a virtualization system. Research conducted by researchers focuses on comparing the performance of Infrastructure as a Service Cloud Computing services with the aim to finding out the strengths and weaknesses of the two types of software with type 1 hypervisor technology, namely Proxmox and Xenserver. The method used in this study is to use action research. The testing scheme conducted in this study is testing CPU load and memory usage, benchmark testing, network traffic testing, and retrieval of service user responsses. The results of testing on Xenserver and Proxmox get good responsse results for CPU load and memory usage testing, benchmark testing, network traffic testing then for responsse results from users Proxmox get a total value of 3848 and Xenserver 3739.